Understanding South Africa’s Changing Positions on International Criminal Justice: Why the country wanted to withdraw from the International Criminal Court (ICC) and why it may remain in the ICC for the time being? - Sarkin,Jeremy Julian (2020)
Abstract1 This article examines why the South African Government decided to withdraw from the Rome Statute for the ICC in 2016. South Africa’s history with international law and international justice are examined to indicate how these matters over time reflect South Africa’s political history and political developments. The next section of the article examines the role the United Nations Security Council plays in relation to the ICC and why that, along with other issues, has led to a greater reluctance by African countries to accept who is judged and who is not. Finally reviewed, is how South Africa’s position on international justice has changed over time, what has caused such change, and whether the country’s withdrawal from the ICC will occur in the future.